Reseña de "Wonder Woman. El feminismo como superpoder" de Elisa McCausland - Guerrero, Isabel (CuCo, Cuadernos de cómic, 2017)
Reseña de "Wonder Woman. El feminismo como superpoder" de Elisa McCausland